Re-discussion on the Relation Between Nihonjijou Course and Cultivation of Intercultural Communication Competence: Indonesian case - Putra, Jeni (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
This study backgrounded by the difficulties to cultivate Intercultural Communication Competence (ICC) in Japanese language learning in Indonesia.In learning Japanese as foreign language, knowing about latest condition and information about Japan is important. Therefore, nihonjijo(knowledge about Japan) course is taught as an essential course. However, with changing world and society, the inevitability of nihonjijouas Japanese cultural course has to be re-discussed. This study aims to find out how nihonjijoucourse can support the cultivation of the ICC, and how it can be reflected in nihonjijoucourse. Literature survey was used in this study. TheresultsshowedthatJapanese cultural knowledgeas material of nihonjijoucourse are ableto cultivate the ICC. However, the learning materials used innihonjijoutend to functioned as communication medium than as culture knowledge. Furthermore, Japanese learnersneed to think and analyse the cultural concept trough their perspective autonomously while teachers need to act as the facilitator who supports the cultural learning process. The teaching of nihonjijoualso need to be integrated with the other coursesto improve its’ effectivity.